THE SATISFACTION OF THAI STUDENTS TOWARDS THE TEST ADMINISTRATION OF THE NATIONAL INSTITUTE OF EDUCATIONAL TESTING SERVICE - Klaharn, Rungrudee (PEOPLE: International Journal of Social Sciences, 2017)
One of the main missions of the National Institute of Educational Testing Service (NIETS) is the measurement and evaluation of Thailand’s education, such as the administration of Thailand’s national test. NIETS has assigned some universities to work as the test centers administering the standardized tests in accordance with the standardized procedures in order that the scores of the standardized tests for grade-12 students could be used as a part of university admission. The objectives of this research were: 1) to study students’ satisfaction,2) to compare the levels of students’ satisfaction towards the NIETS’s testing administration, and 3) to study some problems and suggestions for the effective work improvement. The research samples consisted of 1,024 grade-12 students under the administration of Srinakharinwirot University Test Center, obtained by simple random sampling. The research instruments were the five-rating-scale questionnaires and the interview questions. The content validity of the research instruments were verified by the item-objective congruency (IOC=0.67-1.00). Its reliability was verified by the coefficient of Cronbach alpha = 0.89. The data were analyzed by frequency, percentage; mean, standard deviation, two - way anova and content analysis. The research finding were as follows:1)The research findings indicated that the overall satisfaction was at the high level. 2)The satisfaction levels of the students in the test sites in Bangkok and those in the provincial test sites towards the NIETS’ testing administration were not significantly different; (p = 0.119). However, the satisfaction levels of the male and female students were different at the significant level of 0.05; (p = 0.004)and 3) some suggestions for work improvement.